Effect of positive end-expiratory pressure on lung injury and haemodynamics during experimental acute respiratory distress syndrome treated with extracorporeal membrane oxygenation and near-apnoeic ventilation. (November 2021) - Araos, Joaquin; Alegria, Leyla; Garcia, Aline; Cruces, Pablo; Soto, Dagoberto; Erranz, Benjamín; Salomon, Tatiana; Medina, Tania; Garcia, Patricio; Dubó, Sebastián; Bachmann, María C.; Basoalto, Roque; et al.
Abstract: Background: Lung rest has been recommended during extracorporeal membrane oxygenation (ECMO) for severe acute respiratory distress syndrome (ARDS). Whether positive end-expiratory pressure (PEEP) confers lung protection during ECMO for severe ARDS is unclear. We compared the effects of three different PEEP levels whilst applying near-apnoeic ventilation in a model of severe ARDS treated with ECMO. Methods: Acute respiratory distress syndrome was induced in anaesthetised adult male pigs by repeated saline lavage and injurious ventilation for 1.5 h. After ECMO was commenced, the pigs received standardised near-apnoeic ventilation for 24 h to maintain similar driving pressures and were randomly assigned to PEEP of 0, 10, or 20 cm H2 O ( n =7 per group). Respiratory and haemodynamic data were collected throughout the study. Histological injury was assessed by a pathologist masked to PEEP allocation. Lung oedema was estimated by wet-to-dry-weight ratio. Results: All pigs developed severe ARDS. Oxygenation on ECMO improved with PEEP of 10 or 20 cm H2 O, but did not in pigs allocated to PEEP of 0 cm H2 O. Haemodynamic collapse refractory to norepinephrine ( n =4) and early death ( n =3) occurred after PEEP 20 cm H2 O. The severity of lung injury was lowest after PEEP of 10 cm H2 O in both dependent and non-dependent lung regions, compared with PEEP of 0 or 20 cm H2 O. A higher wet-to-dry-weight ratio, indicating worse lung injury, was observed with PEEP of 0 cm H2 O. Histological assessment suggested that lung injury was minimised with PEEP of 10 cm H2 O. Conclusions: During near-apnoeic ventilation and ECMO in experimental severe ARDS, 10 cm H2 O PEEP minimised lung injury and improved gas exchange without compromising haemodynamic stability.